The Effects of a Ketogenic Medium-Chain Triglyceride Diet on the Feces in Dogs With Idiopathic Epilepsy - Pilla, Rachel (Front Vet Sci, 2020)
Consumption of diets containing medium chain triglycerides have been shown to confer neuroprotective and behavior modulating effects. We aimed to identify metabolic and microbiome perturbations in feces that are associated with consumption of a medium chain triglyceride ketogenic diet (MCT-KD) in dogs with idiopathic epilepsy. We used 16S rRNA gene sequencing to generate microbiome profiles and ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) to generate lipidomic profiles of canine feces. We made comparisons between the MCT-KD, standardized placebo diet and baseline pre-trial diet phases. Consumption of the MCT-KD resulted in a significant increase in the species richness (α-diversity) of bacterial communities found in the feces when compared to the baseline diet. However, phylogenetical diversity between samples (beta-diversity) was not affected by diet. An unnamed Bacteroidaceae species within genus 5-7N15 was identified by LEfSe as a potential biomarker associated with consumption of the MCT-KD, showing an increased abundance (p = 0.005, q = 0.230) during consumption of MCT-KD. In addition, unclassified members of families Erysipelotrichaceae (p = 0.013, q = 0.335) and Fusobacteriaceae (p = 0.022, q = 0.358) were significantly increased during MCT-KD consumption compared to baseline. Blautia sp. and Megamonas sp. instead were decreased during consumption of either placebo or MCT-KD (p = 0.045, q = 0.449, and p = 0.039, q = 0.449, respectively). Bacteroidaceae, including genus 5-7N15, have previously been associated with non-aggressive behavior in dogs. In addition, 5-7N15 is correlated in humans with Akkermansia, a genus known to be involved in the neuroprotective effect of ketogenic diets in mice models of seizures. Five metabolite features, tentatively identified as long chain triglycerides, were significantly higher after consumption of the placebo diet, but no unique features were identified after consumption of the MCT-KD. The data presented in this study highlight significant changes shown in both the fecal microbiome and lipidome as a result of consumption of the MCT-KD. Elucidating the global canine gut response to MCT consumption will improve our understanding of the potential mechanisms which confer anti-seizure and behavior modulating effects. Further studies should aim to characterize the gut microbiome of both dogs with epilepsy and healthy controls.